2016
DOI: 10.3332/ecancer.2016.679
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and predictive implications of Sokal, Euro and EUTOS scores in chronic myeloid leukaemia in the imatinib era—experience from a tertiary oncology centre in Southern India

Abstract: Chronic myeloid leukaemia (CML) is a myeloproliferative disorder. Over the years many prognostic models have been developed to better risk stratify this disease at baseline. Sokal, Euro, and EUTOS scores were developed in varied populations initially receiving various therapies. Here we try to identify their predictive and prognostic implication in a larger population of Indian patients with CML-CP (chronic phase) in the imatinib era.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 33 publications
4
19
0
Order By: Relevance
“…Mean age of our patients was 39.76 years. This is similar to other studies conducted in Southeast Asia but lower than compared to Western countries such as Sweden where mean age of presentation is reported to be 60 years [7][8][9]. The difference could be attributed to demographic characteristics of developing countries or genetic factors.…”
Section: Discussionsupporting
confidence: 88%
“…Mean age of our patients was 39.76 years. This is similar to other studies conducted in Southeast Asia but lower than compared to Western countries such as Sweden where mean age of presentation is reported to be 60 years [7][8][9]. The difference could be attributed to demographic characteristics of developing countries or genetic factors.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings are in line with previous studies from European population and Western population. [ 5 7 14 16 ] According to the EUTOS score, 210 patients (80.7%) and 50 patients (19.2%) were in low-risk and high-risk score respectively, which is similar to the study from European population but in contrast to study from Chinese population by Tao et al . [ 10 11 12 13 ]…”
Section: Discussionsupporting
confidence: 71%
“…These studies indicated the significance of Sokal and Euro score in forecasting the outcome in CML patients and also questioned the validity of the EUTOS scoring system. [ 14 15 16 ] However, contradictory results were suggested by Hoffman et al . in German population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations